2003
DOI: 10.1016/s0006-3223(03)00419-0
|View full text |Cite
|
Sign up to set email alerts
|

Cingulate fasciculus integrity disruption in schizophrenia: a magnetic resonance diffusion tensor imaging study

Abstract: Evidence suggests that a disruption in limbic system network integrity and, in particular, the cingulate gyrus (CG), may play a role in the pathophysiology of schizophrenia; however, the cingulum bundle (CB), the white matter tract furnishing both input and output to CG, and the most prominent white matter fiber tract in the limbic system, has not been evaluated in schizophrenia using the new technology of diffusion tensor imaging (DTI). We used line scan DTI to evaluate diffusion in the CB in 16 male schizoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
242
7
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 350 publications
(286 citation statements)
references
References 66 publications
34
242
7
3
Order By: Relevance
“…In previous investigations (Kubicki et al, 2002b;Kubicki et al, 2003) we showed reduced FA in the region of interest studies of cingulum bundle (CB) and uncinate fasciculus (UF) in schizophrenia. Most recently our group has begun to investigate fronto-temporal abnormalities in schizophrenia using fiber tractography, a method that makes possible the computation of diffusion tensor values along the whole course of the fiber bundles, as opposed to a region of interest approach, where only a small portion of the fiber bundle can be measured.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…In previous investigations (Kubicki et al, 2002b;Kubicki et al, 2003) we showed reduced FA in the region of interest studies of cingulum bundle (CB) and uncinate fasciculus (UF) in schizophrenia. Most recently our group has begun to investigate fronto-temporal abnormalities in schizophrenia using fiber tractography, a method that makes possible the computation of diffusion tensor values along the whole course of the fiber bundles, as opposed to a region of interest approach, where only a small portion of the fiber bundle can be measured.…”
Section: Introductionmentioning
confidence: 88%
“…Mean ages were 39.8 years (SD=9) for patients, and 41.7 (SD=9.3) for controls (F=0.38, df=58, P=0.15). Detailed diagnostic information and inclusion and exclusion criteria are described elsewhere (Kubicki et al, 2003). The local IRB committee at the VA and BWH approved the study and written informed consent was obtained from all subjects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a few works thus far in which cingulum was studied with DTI and a difference of cingulum anisotropy asymmetry was found between control subjects and schizophrenic patients [Kubicki et al, 2003;Wang et al, 2004]. Uncertainty might be increased, however, by manually specifying regions of interest (ROIs) for anterior and posterior parts of cingulum, respectively, in several slices [Wang et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty might be increased, however, by manually specifying regions of interest (ROIs) for anterior and posterior parts of cingulum, respectively, in several slices [Wang et al, 2004]. Kubicki et al [2003] took the cingulum as a whole. To our knowledge, there is no study on the asymmetry of different parts along the cingulum.…”
Section: Introductionmentioning
confidence: 99%